Commodification of The Mangalahat Horbo Bius Ritual on The Samosir Island North Sumatra: A Controversial Show - Mangihut Siregar (MOZAIK HUMANIORA, 2020)
The mangalahat horbo bius ritual is a Batak tradition to offer the best sacrifice to God called Mulajadi na Bolon. This tradition is carried out since they still adhere to the parbaringin flow. The entry of Dutch colonialism into Tapanuli resulted in this tradition being a forbidden tradition. In 2008, the government of Samosir Regency raised this tradition as a show of its purpose as a tourist attraction. Since it was made into a show, there were pros and cons in the community. To explore this attitude research needs to be done. This study uses a qualitative method. The researcher chose the informant purposively followed by the snowball technique. Selected informants: government, religious leaders, and traditional leaders. Data analysis was carried out from the time the study began until the inductive analytic descriptive research results. Theories used as analysis: the theory of power/ knowledge discourse, postcolonial theory, commodification theory, and social practice theory. The theory is used eclectically. The results showed that this ritual performance was counterproductive in increasing the number of visits.